2022
DOI: 10.1007/s00259-022-06013-2
|View full text |Cite
|
Sign up to set email alerts
|

Brain 18F-FDG PET imaging in outpatients with post-COVID-19 conditions: findings and associations with clinical characteristics

Abstract: Background Brain 18 F-FDG PET imaging has the potential to provide an objective assessment of brain involvement in post-COVID-19 conditions but previous studies of heterogeneous patient series yield inconsistent results. The current study aimed to investigate brain 18 F-FDG PET findings in a homogeneous series of outpatients with post-COVID-19 conditions and to identify associations with clinical patient characteristics. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 14 publications
1
24
0
Order By: Relevance
“…However, initial symptoms of COVID-19 are very relevant for long-term cognitive alterations. In this sense, recent research has shown that the symptoms during the initial phase of the disease, including olfactory dysfunction, could be determinants to produce brain alterations ( Goehringer et al, 2022 ). Brain hypometabolism correlated with high inflammation and impaired cognition, assessed with MoCA, and was associated with a higher number of symptoms at the time of the initial infection ( Goehringer et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, initial symptoms of COVID-19 are very relevant for long-term cognitive alterations. In this sense, recent research has shown that the symptoms during the initial phase of the disease, including olfactory dysfunction, could be determinants to produce brain alterations ( Goehringer et al, 2022 ). Brain hypometabolism correlated with high inflammation and impaired cognition, assessed with MoCA, and was associated with a higher number of symptoms at the time of the initial infection ( Goehringer et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, recent research has shown that the symptoms during the initial phase of the disease, including olfactory dysfunction, could be determinants to produce brain alterations ( Goehringer et al, 2022 ). Brain hypometabolism correlated with high inflammation and impaired cognition, assessed with MoCA, and was associated with a higher number of symptoms at the time of the initial infection ( Goehringer et al, 2022 ). This hypometabolism affects frontal, insular and temporal cortices, all regions of the olfactory brain network ( Guedj et al, 2021 ; Goehringer et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GM changes in long COVID have also been documented using 18 fluorodeoxyglucose Positron Emission Tomography (PET) with decreases in metabolic activity among 28 consecutive outpatients, identified mainly in the right frontal and temporal lobes, but including orbito-frontal cortex and internal temporal and frontoparietal lobes [ 42 ]. Other studies involve decreases in cingulate cortex [ 43 ], or bilateral rectus/orbital gyrus including the olfactory gyrus, pre and post central, temporal and fusiform gyri, which consistently enabled infected patients to be distinguished from healthy controls [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…GM changes in long COVID have also been documented using 18 fluorodeoxyglucose Positron Emission Tomography (PET) with decreases in metabolic activity among 28 consecutive outpatients, identified mainly in the right frontal and temporal lobes, but including orbitofrontal cortex and internal temporal and frontoparietal lobes [42]. Other studies involve decreases in cingulate cortex [43], or bilateral rectus/orbital gyrus including the olfactory gyrus, pre and post central, temporal and fusiform gyri, which consistently enabled infected patients to be distinguished from healthy controls [44].…”
Section: Discussionmentioning
confidence: 99%